OPLL Ossification of the Posterior Longitudinal Ligament - Yonenobu, Kazuo; Nakamura, Kozo.; Toyama, Yoshiaki; SpringerLink (Online service) (Tokyo : Springer Japan, 2006)
Ossification of the posterior longitudinal ligament (OPLL) is a hyperostotic condition of the spine with severe neurological deficits. In 1975 the Investigation Committee for OPLL, under the auspices of the Japanese Ministry of Health and Welfare, established diagnostic criteria for the condition, and with growing awareness of OPLL among Japanese researchers and spinal surgeons, the number of patients diagnosed with the condition in Japan has increased in recent years. As knowledge of OPLL has spread, there has also been an increase in the number of reported cases of the condition in other parts of the world: Asia, the United States, and Europe. Until now, however, little has been published on the subject in English; thus the appearance of this present volume is most timely. It brings together information on all aspects of OPLL - epidemiology, etiology, diagnosis, and treatment - with contributions by Japanese researchers and surgeons, including members of the Ministry of Health and Welfare Investigation Committee, and by American surgeons with expertise in the field. This collection of reports on OPLL, amply augmented with illustrations, will be of special interest to orthopedic surgeons and neurosurgeons, and to neurologists, rheumatologists, neuroradiologists, and pathologists.
History of Research -- Epidemiology -- Overview of Epidemiology and Genetics -- OPLL: Disease Entity, Incidence, Literature Search, and Prognosis -- Genetic Susceptibility to OPLL -- Pathology and Pathogenesis -- Overview of Etiology and Pathogenesis -- Etiology and Pathogenesis -- Contribution of Metabolic Conditions to Ossification of the Posterior Longitudinal Ligament of the Spine -- Review of Histopathological Studies on OPLL of the Cervical Spine, with Insights into the Mechanism -- Pathology of Ossification of the Ligamentum Flavum -- Possible Roles of Bone Morphogenetic Proteins and Transforming Growth Factor-?s in the Pathogenesis of OPLL and OLF -- Pathology of Spinal Cord Lesions Caused by Ossification of the Posterior Longitudinal Ligament -- Tiptoe Walking (ttw) Mouse -- Study of Ligament Ossification and Abnormal Glucose Tolerance in the Zucker Fatty Rat -- Experimental Murine Model of Ossification of Spinal Ligaments Induced by Bone Morphogenetic Protein-2 -- Spinal Cord Lesions in Spinal Hyperostotic Mouse (twy/twy) Simulating Ossification of the Posterior Longitudinal Ligament of the Cervical Spine -- Diagnosis of OPLL and OYL -- Diagnosis of OPLL and OYL: Overview -- Clinical Manifestation of Cervical OPLL -- Clinical Manifestations of Thoracic OPLL and OLF -- Diagnostic Imaging of Cervical Ossification of the Posterior Longitudinal Ligament -- Imaging Diagnosis of Thoracic OPLL and OLF -- Electrophysiological Diagnosis of Cervical OPLL Myelopathy -- Treatment of OPLL and OLF -- Overview of Treatment for Ossification of the Longitudinal Ligament and the Ligamentum Flavum -- Pharmacotherapy for Ossification of the Spinal Ligaments: Clinical Trial of Disodium (1-Hydroxyethylidene) Diphosphonate to Inhibit Progression of Ossification of the Posterior Longitudinal Ligament in the Cervical Spine after Posterior Decompression Surgery -- Conservative Treatment of Ossification of the Posterior Longitudinal Ligament in the Cervical Spine -- Choice of Surgical Procedure -- Expansive Laminoplasty -- Expansive Open-door Laminoplasty for Ossification of the Posterior Longitudinal Ligament of the Cervical Spine: Surgical Indications, Technique, and Outcomes -- Double-door Laminoplasty by Splitting Spinous Processes -- Anterior Cervical Decompression for Cervical Myelopathy Caused by Ossification of the Posterior Longitudinal Ligament -- Treatment of OPLL and OLF of the Cervical Spine: Long-Term Results -- Choice of Surgical Procedures for Thoracic Ossification of the Posterior Longitudinal Ligament -- Anterior Decompression and Fusion for Ossification of the Posterior Longitudinal Ligament of the Thoracic Spine: Procedure and Clinical Outcomes of Transthoracic and Transsternal Approaches -- Circumspinal Decompression with Dekyphosis Stabilization for Thoracic Myelopathy due to Ossification of the Posterior Longitudinal Ligament -- Posterior Extensive Cervicothoracic Laminoplasty -- Anterior Decompression Through Posterior Approach for Thoracic Myelopathy Caused by OPLL: Ohtsuka Procedure -- Surgical Treatment for Ossification of the Posterior Longitudinal Ligament of the Thoracic Spine: Outcomes of One-Stage Posterior Decompression with Corrective Fusion Surgery -- Surgery for Ossification of the Ligamentum Flavum -- Computer-Aided Surgery for Ossification of the Spinal Ligaments -- Surgical Treatment of Thoracic Ossification of the Posterior Longitudinal Ligament: Intraoperative Spinal Cord Monitoring -- Intraoperative Ultrasonography for Patients with Ossification of the Posterior Longitudinal Ligament.
Keywords: Medicine; Rheumatology; Neurosurgery; Orthopedics; Medicine & Public Health; Orthopedics; Surgical Orthopedics; Neurosurgery; Rheumatology; Electronic books